Antimutagenic and antioxidant properties of the aqueous extracts of organic and conventional grapevine Vitis labrusca cv. Isabella leaves in V79 cells. Issue 18 (16th September 2016) - Trindade, Cristiano; Bortolini, Giovana Vera; Costa, Bárbara Segalotto; Anghinoni, Joanna Carra; Guecheva, Temenouga Nikolova; Arias, Ximena; Césio, Maria Verónica; Heinzen, Horácio; Moura, Dinara Jaqueline; Saffi, Jenifer; Salvador, Mirian; Henriques, João Antonio Pêgas
ABSTRACT: Grapes are one of the most commonly consumed fruit, in both fresh and processed forms; however, a significant amount is disposed of in the environment. Searching for a use of this waste, the antigenotoxic, antimutagenic, and antioxidant activities of aqueous extracts from organic and conventional Vitis labrusca leaves were determined using V79 cells as model. The antigenotoxic activity was analyzed by the alkaline comet assay using endonuclease III and formamidopyrimidine DNA glycosylase enzymes. The antimutagenic property was assessed through the micronucleus (MN) formation, and antioxidant activities were assessed using 2', 7'-dichlorodihydrofluorescin diacetate (DCFH-DA) assay and 2, 2-diphenyl-1-picrylhydrazyl (DPPH ● ) radical scavenging, as well as with superoxide dismutase (SOD) and catalase (CAT) activity assays. In addition, phenolic content and ascorbic acid levels of both extracts were determined. Data showed that both organic and conventional grapevine leaves extracts possessed antigenotoxic and antimutagenic properties. The extract of organic leaves significantly reduced intracellular reactive oxygen species (ROS) levels in V79 cells, and displayed greater ability for DPPH ● scavenging and higher SOD and CAT activities than extract from conventional leaves. Further, the extract from organic leaves contained higher phenolic and ascorbic acid concentrations. In summary, extracts from organic and conventional grape leaves induced important in vitro biological effects.